Layanan Bimbingan Kelompok untuk Meningkatkan Time Management Skill pada Siswa - Maryati Maryati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
Every human being has the same time in a 24-hour day, as well as high school students who have extraordinary activities. Managing an effective time is not an easy task. The many problems of managing the time experienced by students both for learning, socializing and channeling hobbies make students feel time-chased. Through the Layanan Bimbingan Kelompok in the activity of guidance and counseling students participating in a group, counseling raised the problems they were dealing with relating to daily time management. Group Guidance Activities are carried out according to stages. The predetermined stage is the formation stage, the transitional stage, and the Activity Phase and the Termination Phase. In the Guidance Service, the Group carries out two cycles where in the first cycle participants express and find solutions to their problems daily in problems that relate to time. Based on the results of the first cycle it turns out students experience a lack of time to act. In the second cycle, students are given an explanation of how to manage daily time effectively and efficiently, from observations and student reports it turns out students experience positive changes in time management so that participants in the Group Guidance Service are overcome the problems he experienced so far.